Au croisement de la poésie et de la philosophie : Francis Ponge et Maurice Merleau-Ponty - Millon, Alain; Yang, I-Ning (Labyrinth, 2020)
At the crossroads of poetry and philosophy: Francis Ponge and Maurice Merleau-Ponty The aim of the present article is to clarify the place of the sensitive dictionary in the work of Francis Ponge and to show how it denotes human's relationship to nature. To achieve that, we will use the body question as a measure of the human–nature relationship and apply the phenomenological method that Ponge took over from Merleau-Ponty. It should be noted that Merleau-Ponty rarely makes reference to Ponge's poems, except for a few incisions in his Causeries. As for Ponge, he uses explicitly only the notion of phenomenological reduction to explain his project of sensitive dictionary. However, we will argue that there are many similarities of thought between the philosopher and the poet, which are still unexplored.